2022
DOI: 10.3390/ijerph19042230
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Drug Use Behaviors, Fentanyl Exposure, and Harm Reduction Service Support among People Who Use Drugs in Rural Settings

Abstract: Background: The COVID-19 pandemic has worsened the opioid overdose crisis in the US. Rural communities have been disproportionately affected by opioid use and people who use drugs in these settings may be acutely vulnerable to pandemic-related disruptions due to high rates of poverty, social isolation, and pervasive resource limitations. Methods: We performed a mixed-methods study to assess the impact of the pandemic in a convenience sample of people who use drugs in rural Illinois. We conducted 50 surveys cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 17 publications
3
40
0
Order By: Relevance
“…COVID-19 appeared to shape local drug markets in ways that favored the use of fentanyl even among those who much preferred other drugs. Of particular interest, the qualitative portion of the study unearthed an emerging trend of consuming fentanyl ‘beans’, which during the pandemic became more readily available and cheaper than heroin [ 82 ]. In addition, a lack of access to recourses like naloxone reported by study participants increased the risk of fatal overdose.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 appeared to shape local drug markets in ways that favored the use of fentanyl even among those who much preferred other drugs. Of particular interest, the qualitative portion of the study unearthed an emerging trend of consuming fentanyl ‘beans’, which during the pandemic became more readily available and cheaper than heroin [ 82 ]. In addition, a lack of access to recourses like naloxone reported by study participants increased the risk of fatal overdose.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings regarding the negative impact of the pandemic on PWUD and their access to services are supported by qualitative studies conducted in various global locations. One common theme is reports of changes in the drug market including reduced supply [ 16 18 ], increased prices [ 16 , 19 ], and decreased quality/purity [ 20 ]. These market changes as well as pandemic-related social contact restrictions precipitated increases in risky drug use such as using in isolation [ 17 ], sharing injection equipment [ 18 ], and switching drug type [ 18 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…While this study did not find an increase in online drug transactions [ 61 ], as noted above, searching the Internet for information related to psychedelics does not necessarily imply a desire to purchase them. Surveys of psychedelic users have confirmed that some of them have used Internet-based services for, among other things, harm reduction resulting from the use of psychoactive substances and the difficult access to traditional forms of treatment during the pandemic [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Google Trends also possesses inherent limitations and restrictions; for instance, the search results available through Google Trends are anonymous and only reflect those with Internet access, potentially excluding specific groups of interest, for example, the elderly and underprivileged groups that lack access to the Internet in low- and middle-income countries [ 74 ]. Besides, Google Trends only conveys relative numbers at a percentile scale, and there is no official way to access the absolute numbers.…”
Section: Discussionmentioning
confidence: 99%